Role of innovation in global competition: How innovation drives competitiveness in the global marketplace - Mohd Faizal , Muhammad Fareez Iskandar; Ngor, Phang Yook; Ibrahim, Noorazilah; Muhd Irpan, Hamidah (International Journal of Accounting, Finance and Business, 2025)
Innovation plays an important role in driving competitiveness in the global marketplace. Innovation can help businesses and countries strengthen their economic position while at the same time overcoming global challenges. This conceptual paper explores the relationship between technological innovation and global competitiveness demonstrating how technological advancement can enhance organizational productivity, foster differentiation, and enable greater market agility. It also examines how new goods, services, and business models can affect a country's position in the global economy while highlighting their contributions to international trade and the creation of sustainable value. It provides a better understanding of how innovation shapes competitive advantages while also controlling economic growth and positioning countries as global economic leaders. To this end, it integrates insights from existing literature and conceptual frameworks.